Associations of catechol-O-methyltransferase (rs4680) single nucleotide polymorphisms with opioid use and dose among adults with chronic pain. Issue 1 (January 2019) - Hooten, W. Michael; Biernacka, Joanna M.; O'Brien, Travis G.; Cunningham, Julie M.; Black, John L.
Abstract : Abstract: Catechol-O-methyltransferase (COMT) regulates extracellular catecholamines. A widely studied COMT single nucleotide polymorphism (rs4680) changes the translated amino acid from valine to methionine (Val158Met); the polymorphism has been shown to influence opioid use. The aims of this study were to investigate the influence of COMT Val158Met on the likelihood and dose of opioid use in adults with chronic pain. Adults with chronic pain consecutively admitted to an outpatient pain rehabilitation program were recruited for study participation (N = 298). Individuals were genotyped for COMT Val158Met (rs4680). The polymorphism was analyzed using an additive and codominant genotype model. The distribution of genotypes was 23% (N = 70) for Val/Val, 49% (N = 146) for Val/Met, and 27% (N = 82) for Met/Met (Hardy–Weinberg, P > 0.90). No significant association was observed between opioid use and genotype under the additive model; however, a significant association was observed under the codominant model ( P = 0.027). A post hoc comparison demonstrated that the Met/Met genotype was more likely to use opioids compared with the Val/Met genotype ( P = 0.0089). No significant association was observed between morphine equivalent dose and genotype under the additive model; however, a significant association was observed under the codominant model ( P = 0.0496). A post hoc comparison demonstrated that the Val/Met ( P = 0.019) and Met/Met ( P = 0.043) genotypes used greater morphine equivalent dose compared with the Val/Val genotype. This study extends key knowledge about the influence of the Met/Met genotype and Met allele on opioid use in adults with chronic pain. Abstract : Individuals with the Met/Met genotype were more likely to use opioids and the Met allele was associated with use of greater opioid dosages.